The United States Government Internet Directory 2023 - Ryan, Mary Meghan (Bernan Press, 2023)
Discover the depth of government information and services available online. The United States Government Internet Directory serves as a guide to the changing landscape of government information online. The Directory is an indispensable guidebook for anyone who is looking for official U.S. government resources on the Web. The U.S. government's online information is massive and can be difficult to locate. Many government sites are part of the "Deep Web" with content that does not surface or surface easily even with the most popular search engines. It is more important than ever to have a source that serves as an authoritative guide to the federal Web. The United States Government Internet Directory navigates the maze of data and locates the materials that you seek. The subject-based approach of this book allows you to browse for relevant sites in your field of interest rather than sift through hundreds of search results or try to guess which federal agency to consult. Researchers, business people, teachers, students, and citizens in the United States and around the world can navigate the labyrinthine federal Web with The United States Government Internet Directory. The Directory: contains more than 1,800 Web site records, organized into 21 subject themed chapters includes topics on a wide-range of subjects including employment, energy, defense and intelligence, culture and recreation, and much more provides descriptions and URLs for each site describes sites to help you choose the proper resource notes the useful or unique aspects of the site lists some of the major government publications hosted on the site provides a roster of congressional members with member's Web sites lists House and Senate Committees with committee URLs contains useful, up-to-date organizational charts for the major federal government agencies includes a one-page Quick Guide to the major federal agencies and the leading online library, data source, and finding aid sites identifies the changes in online government information that have occurred place in the past year biog